Integrated in silico–in vitro and pharmacokinetic profiling of Thymus vulgaris-derived metabolites targeting multidrug resistance pathways in extensively drug-resistant Acinetobacter baumannii (muks92) - Abdulkareem, Ali Hazim; Mukhles Ahmed, Mohammed; Abed Latef Al-Meani, Safaa; Abdulkareem, Elham Hazeim (Frontiers in Microbiology, 2025)
BackgroundAcinetobacter baumannii is a major nosocomial pathogen with extensive drug resistance (XDR) driven by β-lactamases, efflux systems, and biofilm formation. Plant-derived metabolites are promising multi-target modulators of these pathways.MethodsTen XDR A. baumannii isolates with strong biofilm and β-lactamase activity were screened; the most resistant (strain muks92) underwent whole-genome sequencing and in-silico analyses. Essential oil from Thymus vulgaris was profiled by GC–MS, identifying o-cymene (32.95%) and gamma-terpinene (16.85%) as dominant constituents. Molecular docking (AutoDock Vina) targeted class D β-lactamase (6T1H), a biofilm-associated regulator (5HM6), and PBP1a/efflux-associated protein (8YR0), with post-docking visualization and AMBER-relaxed stability checks. Antibiofilm activity was quantified by crystal-violet microtiter assay, and ESBL activity by nitrocefin hydrolysis. Multilocus sequence typing (MLST), resistance/virulence gene mining, and mobile genetic element mapping were performed on the genome. Pharmacokinetic/toxicity properties for key metabolites were predicted using ADMET-AI.ResultsGC–MS established a cymene/terpinene-rich chemotype. Docking showed favorable hydrophobic/π–alkyl encapsulation of o-cymene and gamma-terpinene within catalytic or transport pockets of 6T1H, 5HM6, and 8YR0, consistent with steric gating of substrate access. T. vulgaris significantly reduced biofilm biomass versus control (p = 0.0002), and lowered ESBL activity (p = 0.0017). The muks92 genome (3.98 Mb; ST1104) carried a complex resistome including blaOXA-90, blaOXA-72, blaADC-25, blaCARB-14, armA, aac(6′)-Ian, aadA5, sul1/sul2, mph(E)/msr(E), alongside virulence loci (bap, bfmRS, ompA, pgaABCD, csuA/B–E) and siderophore systems (bas/bau/bar), with multiple insertion sequences and an IncA/C2 replicon. ADMET predictions supported good oral absorption and low acute toxicity; gamma-terpinene showed broader tissue distribution (predicted VDss ≈ 7.24 L/kg) and a longer half-life (~4.6 h) than o-cymene.ConclusionT. vulgaris metabolites, particularly gamma-terpinene, exhibit multi-target inhibitory potential against resistance and virulence pathways in XDR A. baumannii (muks92), aligning in-silico interactions with measurable antibiofilm and ESBL attenuation in vitro. Given the predictive nature of docking/ADMET outputs, targeted enzyme kinetics, standardized MIC/MBC testing, cytotoxicity assays, and in-vivo validation are warranted before therapeutic translation.